(3GdeYGOdGJ GdJaGVdjIs - (3fhQI(B, (3OgHjs ((3YeGf(B:s (3OGQ UaGA ddfTQ h GdJhRjY(B,s, 2005)
(3jJfGhd gPG GdcJGH (B: (3GdhMOI GdChdi (B: (3GdeYGOdGJ GdJaGVdjI (B: (3JYGQja (B: (3Jchjf GdeYGOdGJ GdJaGVdjI (B: (3GdKhGHJ GdGNJjGQjI hQHJI eYGOdI JaGVdjI(B-(3GdhMOI GdKGfjI (B: (3GdeYGOdGJ GdJaGVdjI (B: (3WQjbI JjdhQ (B: (3JWHjb JjdhQ Ydi eLehYI GdeYGOdGJ GdJaGVdjI (B: (3WQb Chjd ChjdQ GdeUMMI (B: (3WQjbI GdJfHD hGdJUMjM dGhjdQ(B: (3WQjbI HjcGQO (B: (3WQb Qhfc (B: (3WQb GSJeQGQ GdMd (B((3WQb eJYOOI GdNWhGJ(B)-(3GdhMOI GdKGdKI (B: (3GdeYGOdGJ GdJaGVdjI ef GdQJHI GdChdi hGdOQLI GdChdi (B: (3aUd GdeJZjQGJ (B: (3GdeYGOdGJ GdeJLGfSI (B: (3GdeYGOdGJ GdJi Ydi GdUhQI (B: (3GdeYGOdGJ GdJGeI (B: (3GdeYGOdGJ GdNWjI (B: (3eYGOdI HQfhddi(B-(3GdhMOI GdQGHYI (B: (3JWHjbGJ Ydi GdeYGOdGJ GdJaGVdjI PGJ GdQJHI GdChdi (B: (3JWHjbGJ Ydi GdeYGOdGJ GdJaGVdjI PGJ GdQJHI GdChdi(B-(3GdhMOI GdNGeSI (B: (3GdeYGOdGJ GdJaGVdjI ef GdQJHI GdKGfjI (B: (3fehPL Sha eY eNRhf (B: (3fehPL GdONd Gdbhei(B-(3GdhMOI GdSGOSI (B: (3GdeYGOdGJ GdJaGVdjI GdGYJjGOjI (B: (3GdeYGOdGJ GdNWjI GdeJLGfSI (B: (3GdeYGOdGJ GdNWjI ZjQ GdeJLGfSI (B: (3eSGFd Gdbje GdMOhOjI (B((3GdJNhejI(B) : (3eSGFd Gdbje GdMOhOjI GdTGPI (B: (3OhGd cQjfs
Keywords: (3YGOjI NWjIs; (3eYGOdGJ JaGVdjIs